2015
DOI: 10.1007/s10549-015-3312-8
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of BRCA1 and BRCA2 mutations among young Mexican women with triple-negative breast cancer

Abstract: Various guidelines recommend that women with triple-negative breast cancer should be tested for BRCA1 mutations, but the prevalence of mutations may vary with ethnic group and with geographic region, and the optimal cutoff age for testing has not been established. We estimated the frequencies of BRCA1 and BRCA2 (BRCA) mutations among 190 women with triple-negative breast cancer, unselected for family history, diagnosed at age 50 or less at a single hospital in Mexico City. Patients were screened for 115 recurr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
70
1
10

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(89 citation statements)
references
References 46 publications
8
70
1
10
Order By: Relevance
“…The chance of carrying a germline mutation in BRCA1/2 in very YWBC is almost 10% for patients without a family history of BC and 12% for patients with a family history of BC 65 . In young patients with negative ER subtype BC and high-grade tumors, the probability of having a BRCA1 mutation is close to 30% 66,67 . Significant research has been made to describe the recurrent mutations in Mexican women with BC, and more than 100 deleterious variants have been found to occur among our population 66 .…”
Section: Brca1/2mentioning
confidence: 99%
See 1 more Smart Citation
“…The chance of carrying a germline mutation in BRCA1/2 in very YWBC is almost 10% for patients without a family history of BC and 12% for patients with a family history of BC 65 . In young patients with negative ER subtype BC and high-grade tumors, the probability of having a BRCA1 mutation is close to 30% 66,67 . Significant research has been made to describe the recurrent mutations in Mexican women with BC, and more than 100 deleterious variants have been found to occur among our population 66 .…”
Section: Brca1/2mentioning
confidence: 99%
“…In young patients with negative ER subtype BC and high-grade tumors, the probability of having a BRCA1 mutation is close to 30% 66,67 . Significant research has been made to describe the recurrent mutations in Mexican women with BC, and more than 100 deleterious variants have been found to occur among our population 66 . In unselected women with BC, Torres-Mejía et al described 20 mutations in BRCA1 and 15 in BRCA2.…”
Section: Brca1/2mentioning
confidence: 99%
“…Several studies have examined the prevalence of BRCA mutations in unselected tnbc patients [18][19][20][21] , and their authors have suggested that tnbc patients should be considered for BRCA1 and BRCA2 genetic testing based on the evidence of high BRCA mutation prevalence in unselected tnbc patients. Muendlein et al 18 assessed the prevalence of BRCA mutation in 100 unselected tnbc patients.…”
Section: Discussionmentioning
confidence: 99%
“…They observed a 21% rate of BRCA mutation, and calculated that 38.1%-52.4% of BRCA1/2 mutation carriers would be missed under the current German and Austrian national guidelines for genetic testing, which do not include tnbc as a genetic testing criterion. Villarreal-Garza et al 19 investigated 190 unselected Mexican women with tnbc at the age of 50 years or younger. They found that the prevalence of BRCA mutations was 30.3% in women who were diagnosed at the age of 40 years or younger and 18.3% in those diagnosed between the ages of 41 and 50 years.…”
Section: Discussionmentioning
confidence: 99%
“…There is a consensus in the literature that the prevalence of triple-negative tumors is greater in premenopausal women than in their postmenopausal counterparts 65 . Additionally, women younger than 50 years with triple-negative tumors are more likely to carry BRCA1 gene mutations, which justifies screening for such mutations in this particular group 66,67 .…”
Section: Tumor Biology Heterogeneity Concernsmentioning
confidence: 99%